Enhancing the capacity of water governance to deal with complex management challenges: A framework of analysis. Issue 107 (May 2020) - Pahl-Wostl, Claudia; Knieper, Christian; Lukat, Evelyn; Meergans, Franziska; Schoderer, Mirja; Schütze, Nora; Schweigatz, Daniel; Dombrowsky, Ines; Lenschow, Andrea; Stein, Ulf; Thiel, Andreas; Tröltzsch, Jenny; et al.
Highlights: Framework for complex coordination challenges in water governance and management. Diagnostic approach supports context-sensitive assessment. Structured case study comparison enhances strength of diagnosis. Abstract: Despite numerous efforts to promote and implement more integrated approaches, coordination problems persist and impede sustainable water governance and management. This paper introduces a framework for guiding a transdisciplinary diagnostic approach (i.e. a context-sensitive assessment of multi-level water governance, which is combined with a change management process) to address such coordination problems. The approach aims at addressing some of the challenges identified in scientific scholarship and water governance practice by combining context-specific participatory assessments of individual cases with comparative case analysis guided by a generic conceptual framework. The focus is on implementation processes at regional and local scale and their embedding in a multi-level water governance system and a specific environmental and societal context. A coherent approach and formalized representation across individual cases is essential to develop cumulative knowledge and to improve the diagnostic strength of the approach. Based on a broad literature review and exploratory study of multiple, diverse cases conceptual framework identifies a variety of factors that are expected to be important for understanding the performance of environmental governance and management systems. The paper makes explicit the hypotheses on relationships between core variables that resulted from framework development. The framework, including the collection of hypotheses, offers a structured approach for analysing a phenomenon as complex and multi-facetted as coordination. It allows identification of multiple pathways that may lead an improvement or a decline in performance, respectively. The framework can find more widespread application in supporting comparative case study analyses with a focus on improving the understanding of policy implementation also beyond the field of water governance and management.